A knowledge audit model of Botho College focussing on core processes : an analysis of alignment of knowledge needs and organisational performance - Makambe U (2014)
Please help populate SUNScholar with the full text of SU research output. Also - should you need this item urgently, please send us the details and we will try to get hold of the full text as quick possible. E-mail to scholar@sun.ac.za. Thank you.